Effect of patient navigation on colorectal cancer screening in a community-based randomized controlled trial of urban African American adults - Horne, Hisani N.; Phelan-Emrick, Darcy F.; Pollack, Craig E.; Markakis, Diane; Wenzel, Jennifer; Ahmed, Saifuddin; Garza, Mary A.; Shapiro, Gary R.; Bone, Lee R.; Johnson, Lawrence B.; Ford, Jean G. (Cancer causes & control, 2015)
Purpose: In recent years, colorectal cancer (CRC) screening rates have increased steadily in the USA, though racial and ethnic disparities persist. In a community-based randomized controlled trial, we investigated the effect of patient navigation on increasing CRC screening adherence among older African Americans. Methods: Participants in the Cancer Prevention and Treatment Demonstration were randomized to either the control group, receiving only printed educational materials (PEM), or the intervention arm where they were assigned a patient navigator in addition to PEM. Navigators assisted participants with identifying and overcoming screening barriers. Logistic regression analyses were used to assess the effect of patient navigation on CRC screening adherence. Up-to-date with screening was defined as self-reported receipt of colonoscopy/sigmoidoscopy in the previous 10 years or fecal occult blood testing (FOBT) in the year prior to the exit interview. Results: Compared with controls, the intervention group was more likely to report being up-to-date with CRC screening at the exit interview (OR 1.55, 95 % CI 1.07–2.23), after adjusting for select demographics. When examining the screening modalities separately, the patient navigator increased screening for colonoscopy/sigmoidoscopy (OR 1.53, 95 % CI 1.07–2.19), but not FOBT screening. Analyses of moderation revealed stronger effects of navigation among participants 65–69 years and those with an adequate health literacy level. Conclusions: In a population of older African Americans adults, patient navigation was effective in increasing the likelihood of CRC screening. However, more intensive navigation may be necessary for adults over 70 years and individuals with low literacy levels.